Wuzhi Wuyang-Traditional Chinese Medicine Prevention and Treatment of Malignant Tumor - Han, Baojin; Tan, Ying; Cai, Ruijuan; Mao, Qiyuan; Zhang, Chuchu; Zhong, Yiwei; Lin, Hongsheng (Zhongliu fangzhi yanjiu, 2025)
In response to the clinical needs of cancer treatment and rehabilitation, Professor Lin Hongsheng proposed the Wuzhi Wuyang (five treatments and rehabilitation) concept on the basis of years of clinical experience and the Guben Qingyuan (consolidate the foundation and clear the source) theory. Wuzhi Wuyang emphasizes the importance of treatment and rehabilitation and aims to provide personalized and stage-specific treatment and rehabilitation plans by integrating the advantages of traditional Chinese medicine (TCM) and modern medicine to achieve comprehensive life-cycle management for patients with cancer. The proposal of Wuzhi Wuyang has provided new ideas and methods for the treatment, prevention, and rehabilitation of cancer, along with valuable references for clinical practice and academic research. This article summarizes the connotation of Wuzhi Wuyang and its application in the comprehensive management of cancer prevention and treatment with TCM.